Diagnosis, management and prognosis of familial hypercholesterolaemia in a UK tertiary cardiac centre. Issue 1 (1st January 2019) - Barbir, Mahmoud; Breen, Jane; Neves, Emma; Priestley-Barnham, Lorraine; Lazem, Fawzi; Grocott-Mason, Richard
ABSTRACT: Objective : To describe demographic characteristics, current local clinical management and outcomes for patients with familial hypercholesterolaemia (FH) managed at the Royal Brompton and Harefield NHS Foundation Trust (RBHT), a specialist UK tertiary cardiac centre. Research design and methods : A local service evaluation of patients with FH was conducted by RBHT. Patients were identified from local FH databases and medical records based on pre-defined eligibility criteria. Descriptive statistics were performed. Main outcome measures : Proportion of patients with cardiovascular (CV) events during the period of follow-up; per cent change in low-density lipoprotein cholesterol (LDL-C) between highest untreated and most recent measurement; description of patient characteristics and treatment pathways. Results : The final evaluation sample included 306 patients whose first contact with the RBHT FH service was between November 1991 and February 2015. Patients were followed up until 2016 (median 4.4 years, range 1.2–24.9). Forty-three per cent (131/306) of patients had genetically confirmed FH and 56% (172/306) did not but meet a modified Simon Broome criteria. One fifth (20%, 60/306) had at least one CV event prior to their first contact with the service, mainly angioplasty (15%, 45/306) and MI (10%, 32/306). Thirty-five patients (11%) had CV events during the period of follow-up, occurring at a mean of 5.2 years after first contact. Of 269 "current" patients (i.e. patients with at least one contact with the service in the previous 3 years) 90% (241/269) were prescribed statins, with adverse events experienced by 30% (73/241). Eleven patients received lipoprotein apheresis. Only 34% (49/143) of patients had a reduction of ≥50% between the highest untreated and most recent LDL-C measurement. Conclusions : Results highlight the challenges of diagnosing and management of this high risk patient group whilst reducing CV events. Future work should focus on characterisation of patient subgroups and optimising treatment with novel therapeutic agents.